Catálise heterogênea na produção de biodiesel: comparação entre a sílica híbrida Si-MCM-48 e as zeólitas X e Y - Ferrarini, Ana Carolina Ferraz [UNIFESP] (2020)
Biodiesel can replace petroleum diesel in virtually any engine, without requiring further modifications. It’s production can be accomplished by several methods, and the alkaline transesterification reaction is the most used. Industrially, biodiesel is still largely produced by alkaline catalysis in homogeneous solution, using metal alkoxides as catalysts and varying the type of vegetable oil, according to the region, however, the production of biodiesel can also be performed by heterogeneous catalysis. This strategy offers technical and environmental advantages over homogeneous catalysis, as it favors the purification of the alkyl monoesters, allows the recycling of the solid catalyst over its useful life and minimizes the generation of effluents. Several solids have been proposed as potential catalysts for the synthesis of biodiesel, and their performance as catalysts is naturally related to the nature of the acid or basic sites found in these materials. The object of study in this paper the biodiesel production processes was studied using homogeneous catalysis with NaOH, and heterogeneous with hybrid silica Si-MCM-48 and zeolites X and Y modified to their acid form, and comparison of results obtained, bringing scientific novelty. The formed products were analyzed via Hydrogen Nuclear Magnetic Resonance (1H NMR), proving the formation of the product (biodiesel). After comparisons, it was proven that the use of HX and HY zeolites can be considered for the replacement of the homogeneous catalyst (NaOH), since their performance is very similar, reaching high levels of conversion in small periods of time (conversions close to 100% in 40 min reaction). The hybrid silica Si-MCM-48 did not perform as expected from a basic catalyst, since the surfactant responsible for the formation of catalytic sites is leached during the reaction, causing the conversion to reach maximum levels of approximately 60%. Thus, it is understood that zeolites in their acid form are materials of interest and that can be considered for implementation studies of implementation in industry.